Penerapan Terapi Komplementer Dzikir terhadap Skala Nyeri Pasien Post Operasi di Ruang Mawar RSUD Dr. Soehadi Prijonegoro Sragen - Friska Nanda Pertiwi; Ika Silvitasari; Yani Indrastuti (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
The problem that many postoperative patients experience is pain complaints caused by surgical wounds or surgical wounds. So that it results in patients not being happy, restless, and various disorders that are felt differently. So non-pharmacological therapy is needed to overcome the pain felt, namely by doing dhikr therapy. the application of dhikr relaxation therapy was carried out, namely to see how the application of dhikr relaxation therapy to the scale of pain in postoperative patients. Using a descriptive method in the form of a case study of the two respondents by focusing on the implementation of dhikr relaxation therapy to reduce postoperative pain by giving it for 3 days. Dhikr relaxation therapy has an effect on the change in the postoperative pain scale so that the acute pain experienced by patients is reduced. Patient 1 from scale 6 to scale 3 and the second patient from scale 6 to scale 2. Dhikr therapy in postoperative patients with pain is effectively able to reduce surgical wound pain and can be developed in future studies.